PEMANFAATAN VIDEO ANIMASI DARI PLATFORM YOUTUBE SEBAGAI MEDIA PEMBELAJARAN FIQIH UNTUK MENINGKATKAN HASIL BELAJAR SISWA MADRASAH IBTIDAIYAH - Zuhro Wardi Abdul Qois Idris, Imam; Kholil, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the utilization of animated videos from the YouTube platform as a learning medium in Fiqh lessons, particularly in the material of prayer practice, to improve student learning outcomes at MI Nurul Mun’im. This research employed a descriptive qualitative approach conducted in a natural setting. The subjects of the study were second-grade students. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that the use of YouTube-based animated videos significantly increased students’ active participation and engagement during the learning process. The number of students who actively asked questions and practiced prayer movements improved compared to conventional lecture-based instruction. Furthermore, students demonstrated better understanding of prayer sequences, recitations, and movements accuracy after the implementation of animated video media. The study also revealed increased learning motivation, as students showed greater enthusiasm and expressed interest in rewatching the videos independently. Despite minor technical constraints such as internet connectivity, the role of the teacher as a facilitator remained crucial in guiding and reinforcing students’ understanding. Overall, the integration of animated videos from YouTube in Fiqh learning effectively enhances cognitive and affective learning outcomes and supports innovative digital-based instruction in Madrasah Ibtidaiyah.